Avaliação dos efeitos do laser Er,Cr:YSGG em defeitos ósseos críticos e no tratamento de doença periodontal induzida em ratos submetidos a inalção de fumaça de cigarro - Pavone, Chaine [UNESP] (2014)
The aim of this study was to evaluate the influence of the Er, Cr: YSGG laser in critical-size defects and in the treatment of periodontal disease in rats subjected to cigarette smoke inhalation. It was used 180 rats divided into 6 groups: Cigarette Smoke scaling (CSRP) - cigarette smoke inhalation (CSI), induction of periodontal disease (IPD) and scaling and root planing (SRP); Cigarette Smoke Laser (CL) - CSI, IPD and Er,Cr:YSGG laser irradiation; Cigarette Smoke SRP+Laser (CSRP+L) - CSI, IPD and RAR + Laser; Scaling and root planning (SRP) IPD, SRP; Laser (L) - IPD and Laser; Scaling and root planning + Laser (SRP+L) - IPD and SRP followed by Laser. The histometric results showed that in all groups analyzed it was observed a tendency to bone formation over the periods, however this difference was only significant in the CSRP comparing 15 and 30 days (p<0,05). The intergroup comparison showed that the 15-day period, the percentage of bone area was greater in the FL group compared to FRAR group. No difference was observed in the groups not exposed to cigarette smoke inhalation. In reaction by real-time PCR, L and SRP + L groups showed higher expression of VEGF at 30 days (p <0.05) compared to 15 days (p <0.01). The FRAR group showed lower expression of VEGF at 30 days (p <0.05) compared to 15 days. For creation of the defects, 100 rats were divided into 4 groups: GT: creation of the defect with trephine; GL: defect created with the laser; GFT: IFC and creation of defect with trephine; GFL: IFC and creating defect with the laser. The results showed that histometrically, the defect was lower in the trephine group at 30 21 and 60 days compared to the initial period (p <0.05). In the laser group this decrease occurred at 15, 30 and 60 days compared to the initial period (p <0.05, p <0.01, p <0.001) and at 30 and 60 days compared to 7 days (p <0, 05 and p <0.01). In animals exposed to cigarette...(Com'plete abstract click electronic acess)